Analisis Penerapan Activity Based Costing Method Dalam Pencapaian Laba Perusahaan (Study Pada Industri UKM DiJabodetabek) - Herry Respati (P3M Politeknik Negeri Bengkalis, 2025)
Small and Medium Enterprises (SMEs) in Indonesia face significant challenges in maintaining profitabilitythrough optimal operational efficiency in the increasingly competitive global economy. Activity-Based Costing(ABC) has emerged as a superior cost management method compared to traditional costing systems, yet itsimplementation in SMEs, particularly in developing countries like Indonesia, remains understudied. This studyanalyzes the implementation of Activity-Based Costing methods in achieving company profits within the SMEindustry in Jabodetabek, examining implementation levels, profitability impacts, and effectiveness factors. Aqualitative case study approach was employed, utilizing purposive sampling to select 10 culinary SMEs inJabodetabek that maintain accounting records through applications. Data collection involved in-depth interviews(60-90 minutes per respondent) and secondary document analysis. Thematic analysis was used for datainterpretation, with validity ensured through data triangulation and member checking. Findings reveal that ABCimplementation among culinary SMEs remains in developmental stages with limited conceptual understandingyet intuitive partial application. Three main themes emerged: limited conceptual understanding, intuitive partial implementation, and operational recording challenges. SMEs demonstrated creative adaptation by simplifyingABC principles, resulting in improved costing accuracy (15-30% cost corrections), optimized pricing strategies,and identification of cost-saving opportunities leading to increased profit margins. The study contributesacademically by developing an ABC adaptation model suited to SME characteristics and practically by providingimplementation guidelines. Managerial mindset and learning orientation proved more determinant than formaleducational background for successful ABC implementation.